Meizhou Dongpo Restaurant : entrepreneurship, leadership and culture - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
On June 6, 1996, a restaurant in northeast Beijing quietly opened. The 300-square-meter restaurant featured an elegant, warm and luxurious decoration style. Its walls were covered with poems, essays, paintings, calligraphies and literary quotations of Su Dongpo, a great literature maestro in the Song Dynasty. The menu's main dish ingredients as well as seasonable fruits, vegetables and freshwater fishes all came from Sichuan. Employees were primarily recruited from Sichuan. It was the first Meizhou Dongpo Restaurant.